Prospective Comparison of Reduced-Iodine-Dose Virtual Monochromatic Imaging Dataset From Dual-Energy CT Angiography With Standard-Iodine-Dose Single-Energy CT Angiography for Abdominal Aortic Aneurysm - Agrawal, Mukta D.; Oliveira, George R.; Kalva, Sanjeeva P.; Pinho, Daniella F.; Arellano, Ronald S.; Sahani, Dushyant V. (American journal of roentgenology (1976), 2016)
The purpose of this study was to compare the image quality of reduced-iodine-dose single-source dual-energy CT angiography (CTA) with that of standard-iodine-dose single-energy CTA in examinations of patients with abdominal aortic aneurysm and to assess the effect of the concentration of iodinated contrast medium on intravascular enhancement and image quality of reduced-iodine-dose CTA. In a prospective randomized clinical trial, 66 consecutively registered patients with abdominal aortic aneurysm who had previously undergone single-energy CTA (30-37 g I) underwent follow-up CTA at a reduced dose (21-27 g I) of iodinated contrast medium of either 270 mg I/mL (n = 33) or 320 mg I/mL (n = 33). Two readers independently evaluated virtual monochromatic imaging datasets (40-140 keV) and single-energy CTA images for image quality and noise and their preference for optimal energy virtual monochromatic imaging dataset. A value of p < 0.05 was considered statistically significant. All 66 dual-energy CTA examinations were rated diagnostic with mean image quality and image noise scores of 4.8 and 4.5 for reader 1 and 3.8 and 3.4 for reader 2 compared with single-energy CTA results of 4.5 and 4.2 for reader 1 and 4.5 and 4.1 for reader 2. Low-energy virtual monochromatic images (40-60 keV) from reduced-iodine-dose (28%) dual-energy CTA had significantly higher intravascular aortic attenuation (26-185%) and contrast-to-noise ratio (CNR) (20-25%) than standard-iodine-dose single-energy CTA images (p < 0.0001). No significant difference was found between patients who received 270 and those who received 320 mg I/mL with respect to intravascular aortic attenuation (p = 0.6331) or CNR (p = 0.9775). Low-energy virtual monochromatic imaging datasets from reduced-iodine (24 g I) single-source dual-energy CTA of the abdomen provide up to 185% higher attenuation and 25% higher CNR than standard-iodine-dose (33.3 g I) single-energy CTA while offering a wide range of energy settings irrespective of the concentration of IV contrast medium used.